LCST phase behavior of benzo-21-crown-7 with different alkyl chains - Deng, Yan; Li, Xing; Zhang, Qiao; Luo, Zheng; Han, Chengyou; Dong, Shengyi (Beilstein Journal of Organic Chemistry, 2019)
The introduction of hydrophobic units into crown ethers can dramatically decrease the critical transition temperature of LCST and realize macroscopic phase separation at low to moderate temperature and concentration. Minor modifications in the chemical structure of crown ethers (benzo-21-crown-7, B21C7s) can effectively control the thermo-responsive properties.
Keywords: crown ethers; hydrophobic units; lower critical solution temperature; LCST; thermo-responsiveness; supramolecular chemistry